The use of chicoric acid from Echinacea purpurea as a feed additive in poultry nutrition. Issue 1 (8th December 2017) - SAEED, M.; BABAZADEH, D.; ARAIN, M.A.; NAVEED, M.; SHAH, Q.A.; KAMBOH, A.A.; MOSHAVERI, A.; MODARRESI-GHAZANI, F.; HEJAZI, V.; CHAO, S.
Abstract : Echinacea purpurea is one of the most widely used medicinal herbs that is of interest to animal scientists due to its valuable immuno-stimulatory and anti-inflammatory properties. It is thought that it activates the immune system through stimulating T-cell production, lymphocytic activity, phagocytosis, cellular respiration and inhibiting the secretion of the hyaluronidase enzyme. Chicoric acid (CA) is a major active constituent of Echinacea purpurea . The CA content in roots ranges between 16.80-24.30 mg/g which has gained a lot of renown due to its promising bio-activities. CA has shown to simulate growth promoters and have antioxidant, anti-diabetic, anti-inflammatory, anti-HIV, anti-bacterial, hypoglycaemic and hepatocyte protective properties. There have been very few studies relevant to CA and its use in poultry diets. Previously published studies have included pharmacological and nutritional investigations in the poultry industry. CA could be used as an alternative to antibiotics, and may improve meat quality and health status in broiler chickens.